Mapping Function from Dynamics: Future Challenges for Network-Based Models of Protein Structures - Pacini, Lorenza; Dorantes-Gilardi, Rodrigo; Vuillon, Laurent; Lesieur, Claire (Frontiers in Molecular Biosciences, 2021)
Proteins fulfill complex and diverse biological functions through the controlled atomic motions of their structures (functional dynamics). The protein composition is given by its amino-acid sequence, which is assumed to encode the function. However, the discovery of functional sequence variants proved that the functional encoding does not come down to the sequence, otherwise a change in the sequence would mean a change of function. Likewise, the discovery that function is fulfilled by a set of structures and not by a unique structure showed that the functional encoding does not come down to the structure either. That leaves us with the possibility that a set of atomic motions, achievable by different sequences and different structures, encodes a specific function. Thanks to the exponential growth in annual depositions in the Protein Data Bank of protein tridimensional structures at atomic resolutions, network models using the Cartesian coordinates of atoms in a protein structure as an input have been used over twenty years to investigate protein structure-function relationships. Typical network measures and ad-hoc measures are now available to probe structural motions or perturbations related to mutations combining networks with experimental studies or Molecular Dynamics simulations. The perspective is now to extend network methods to establish whether the structures of sequence variants having the same function share dynamic features that are different from the dynamic features of structures of sequence variants having different functions, making the link between dynamics and function. An additional challenge is to focus on the slow dynamics that underlie biological functions.